What Role for Electric Vehicles in the Decarbonization of the Car Transport Sector in Europe? - Christina Littlejohn; Stef Proost (Center for Economic Studies and ifo Institute (CESifo), 2019)
The transport sector is the only sector where carbon emissions continue to grow. This has led policy makers to propose ambitious policies to reduce emissions in the car sector, in particular fuel efficiency standards, portfolio mandates for Electric Vehicles and purchase taxes or subsidies. A portfolio mandate describes a minimum quota of annual electric vehicle sales. We use a two-period model for the car manufacturing sector to compare the cost efficiency of these policies. The model has gasoline fuelled cars (GV) compete with battery electric cars (EV). Both types of cars have endogenous technological progress that is triggered by environmental policies, including tradable fuel efficiency standards, portfolio mandates, carbon taxes, purchase taxes and R&D subsidies. EVs can serve as batteries that permit grid operators to shift off peak (renewable) electricity to peak hour supply. The model is calibrated to evaluate the EU policy to reduce average carbon emissions of cars by 37,5% in 2030. We assess the cost-efficiency of three types of policy instruments evaluating production costs, fuel costs, and externalities. We find that a fuel efficiency standard targeting gasoline cars achieves emission reductions at a much lower cost than a portfolio mandate for Electric cars.
Keywords: Q54; Q58; 330; electric vehicles; EU climate policy; climate change; portfolio mandate; R&D